REDUPLIKASI BAHASA INGGRIS DAN BAHASA SAHU (ANALISIS KONTRASTIF) - WABULA, PUJAYANTI NOPIANA; KODONG, FENTJE; MANUS, JEANE ANGELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This study is an attempt to describe and analyze the English and Sahu language specifying on the process of reduplications, by also to contrast the forms, function and meaning of reduplications of both languages. The English data are collected from several English books, about reduplication, thesis, related theories from library and internet. Whereas Sahu language are collected from the Sahu language dictionary, the Sahu language bible and also collected from informants of Sahu language in Tibobo Village. The descpritive method is used to describe and analyze the reduplication in both languages. After describing the process of reduplication in English and Sahu language, the writer makes a contrastive analysis to find out the similarities and differences of both languages. Theoretically, this investigation is going to give a contribution in morphological analysis especially in reduplication, for development of linguistics. The result of this investigation shows that English has a full reduplication phonemic variations. Whereas Sahu language has many types of reduplication, such as: full reduplication, partial reduplication, and the reduplication with affixation. Keywords: Reduplication, English and Sahu Language, Contrastive Analysis.